Systemic Disorders, Comorbid Pathology and Gastric Function in Patients with Type 2 Diabetes Mellitus (Eurasian Medical Research Periodical, 2023)
In this work, a study of the motor evacuation function of the stomach, the prevalence of pathology of the gastrointestinal tract, the state of autonomic regulatory mechanisms in patients with type 2 diabetes mellitus was conducted. An assessment was made of the relationship of disorders of general vegetative mechanisms and regulation of gastric function with the duration of the disease, compensation of carbohydrate metabolism and the labile course of diabetes. The obtained results clearly demonstrate the need to assess the state of motor evacuation function of the stomach in patients with type 2 diabetes mellitus, regardless of the age of the disease, for subsequent correction of the identified disorders in order to improve diabetes compensation and prevent hypoglycemic conditions.